A good wife? a theological challenge to cultural practices and gender-based violence in Rushinga, Zimbabwe - Van Wyk, Tanya (University of Pretoria, 2025)
Thesis (PhD (Dogmatics and Christian Ethics ))--University of Pretoria, 2024.